PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN DENGAN KONSERVATISME AKUNTANSI SEBAGAI VARIABEL MODERASI - Ditama, Anhar; Juliarto, Agung (Diponegoro Journal of Accounting, 2024)
This stuudy aims to analyze the influence of company ownership as measured by the independent variables ownership concentration, managerial ownership and institutional ownership on company performance as measured by the dependent variable return on assets (ROA) with accounting conservatism as a moderating variable.This study uses population made up by manufacturing sector companies listed on the Indonesia Stock Exchange during the 2017-2019 period. The sample in this study was determined using a purposive sampling method, which then obtained 52 companies or 156 observation data and after eliminating outlier data, 102 observation data were obtained which could be analyzed. The data used is secondary data in the form of the company's annual financial reports obtained through the official IDX website at www.idx.co.id and the company's official website. This research uses multiple linear regression analysis methods to analyze the data.The results of statistical tests in this research found that concentrated ownership has positive results in increasing company performance. These results are contrary to the first hypothesis set. It is the same with the second and third hypotheses where the results show that managerial ownership and institutional ownership have a negative but not significant influence. Accounting conservatism as a moderating variable influences the relationship of the three independent variables to the dependent variable. The results of the analysis show that the fourth and sixth hypotheses are accepted with a positive influence and significant value, while the fifth hypothesis is rejected with a positive influence but the value is not significant.